ADHERENCE TO INSULIN TREATMENT IN CHILDREN WITH TYPE I DIABETES MELLITUS AT A HOSPITAL IN MALAYSIA - Lai Ying, Chong; Shah, Noraida Mohamed (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study aimed to evaluate adherence to insulin treatment and identify factors that influence adherence in children with T1DM at a tertiary care hospital in Malaysia. Methods: Patients were identified from the pharmacy computer system based on the prescribed insulin therapy from 2010 to 2014. Medical records of screened patients were then retrieved from the medical record department. Adherence was assessed via the medication possession ratio (MPR) and glycated hemoglobin A1c value. Patients were classified as adherent or non-adherent if the MPR calculated for the prescribed insulin regimen was â‰¥80% or <80%, respectively. Patients with A1c values <7.5% based on medical records were also classified as adherent. Results: A total of 57 patients were included in this study, with a 57.9% male predominance and a mean age of 14.39 Â± 3.41 years. Thirty-nine (68.4%) and three patients (5.3%) were classified as adherent to insulin treatment according to MPR and A1c values, respectively. Poor agreement between the MPR and A1c value in determining adherence was found based on kappa analysis (kappa = âˆ’0.108, p=0.009). There was no association between age, sex, race, presence of comorbidities, or duration of T1DM diagnosed and adherence based on the A1c value (p>0.05). These predictors were also found to be insignificant based on multiple logistic regression analysis (p>0.05). Conclusion: Adherence to insulin treatment based on the A1c measurement was generally poor among children with T1DM. Further prospective research should be performed in this area to identify reasons for the non-adherence to insulin treatment so that appropriate interventions can be instituted to improve adherence and ultimately prevent complications from the disease.Â